Brasil: Globalização e Regionalização (GEOgraphia, 2009)
Resumo O processo de globalização não é um processo recente, e vem sempre associado a distintas dinâmicas de regionalização. No caso brasileiro, sua inserção aos circuitos globais começa no período colonial, e diferentes regionalizações vão se sucedendo no tempo. A globalização, longe de ser simplesmente um processo unificador. realiza permanentes diferenciações do espaço geográfico. Palavras-chave: Globalização, Regionalização. Espaço Brasileiro.Abstract The process of globalization is not a recent process. and it is always associated with different dynamics of regionalization. In Brazil, its insertion to global circuits begins at the colonial period, with different regionalizations through each historical phase. So, the globalization is not simply an unifying process but it produces constant differentiation at geographic space. KeThe process of globalization is not a recent process. and it is always associated with different dynamics of regionalization. In Brazil, its insertion to global circuits begins at the colonial period, with different regionalizations through each historical phase. So, the globalization is not simply an unifying process but it produces constant differentiation at geographic space. Kevwords: Globalization, Regionalization, Brazilian Space.vwords: Globalization, Regionalization, Brazilian Space.